Second-generation human rights in the constitutions of selected Balkan countries - Jarczyński, Krzysztof (Mundus Slavicus I, 2025)
The article presents research on the constitutions of selected Balkan countries. Its aim is to check whether they include economic, social, and cultural rights, which are classified as second-generation human rights. The study shows that each constitution contains these rights, but the way in which they are formulated is different. The work is based on comparing constitutional legal norms. It also briefly discusses the idea of second-generation human rights.